2018
DOI: 10.5194/hess-22-159-2018
|View full text |Cite
|
Sign up to set email alerts
|

Multiconfiguration electromagnetic induction survey for paleochannel internal structure imaging: a case study in the alluvial plain of the River Seine, France

Abstract: Abstract. The La Bassée floodplain area is a large groundwater reservoir controlling most of the water exchanged between local aquifers and hydrographic networks within the Seine River basin (France). Preferential flows depend essentially on the heterogeneity of alluvial plain infilling, whose characteristics are strongly influenced by the presence of mud plugs (paleomeander clayey infilling). These mud plugs strongly contrast with the coarse sand material that composes most of the alluvial plain, and can crea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Several errors could be introduced from the variation in orientation of the CMD device (caused by thorn bushes and localized topography) when crossing the ERT survey lines. The field constraints led to different georeferencing accuracies between the geophysical and direct excavation data that could have also affected the data acquisition (as shown by Rejiba et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several errors could be introduced from the variation in orientation of the CMD device (caused by thorn bushes and localized topography) when crossing the ERT survey lines. The field constraints led to different georeferencing accuracies between the geophysical and direct excavation data that could have also affected the data acquisition (as shown by Rejiba et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ERT inverted resistivity model as a reference to calibrate EMI data has been proved to be a successful and replicable calibration strategy (Lavoué et al, ). Previous hydrogeological studies (Mester, van der Kruk, Zimmermann, & Vereecken, ; Rejiba et al, ; von Hebel et al, ) have shown the suitability of EMI methods in contexts of relatively large conductivity, such as with features that have large conductivity exceeding 30 mS m −1 (33 Ω m) surrounded by a geological background of ~15 mS m −1 (67 Ω m). The reference ERT model also helped to (a) counter the poor sensitivity of EMI to resistive grounds and (b) eliminate equivalent models with layer parameters (thicknesses and conductivities) that can resolve EMI data but that are unrealistic with regard to the site context (Jadoon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic induction has shown considerable potential for characterization and monitoring of soil geophysical properties at field scale (Abdu et al, 2007; Triantafilis and Monteiro Santos, 2009, 2010, 2013; Jadoon et al, 2017; Altdorff et al, 2018; Rejiba et al, 2018; Robinet et al, 2018). Electromagnetic induction returns EC a (or σ a , mS m −1 ), which is a cumulative response of the subsurface electrical conductivities.…”
mentioning
confidence: 99%
“…In relatively small, shallow streams such a method is challenging to use because of the need to install electrodes. The electromagnetic induction (EMI) technique is a more practical method for detecting local shallow heterogeneities beneath surface water bodies in a continuous manner and hence is being increasingly applied in the field of hydrology (Binley et al, 2013;Gaona, Meinikmann, & Lewandowski, 2019;Rejiba et al, 2018). EMI surveys provide an integrated measure of the apparent electrical conductivity over a depth that is a function of the separation between transmitter and receiver coils.…”
Section: Introductionmentioning
confidence: 99%